Some socio-demographic characteristics of cured patients of COVID-19 discharged from dedicated covid care center in metropolitan region - Balaram Gurav, Ravindra; Yadav, Amit; Nair , Aishwarya (International Journal Of Community Medicine And Public Health, 2023)
Background: As per ICMR study in April 2020, around 30% of all the proven cases of COVID-19 were asymptomatic and various modeling studies had estimated that 40% of the transmission was by the asymptomatic patients. So, it was decided to isolate all such patients at dedicated covid care centers in order to stop the transmission of the corona virus. Methods: This was a cross-sectional study conducted at a dedicated covid care center (DCCC) in a metropolitan region from 27 June, 2020 to 10 July, 2020. All the cured asymptomatic confirmed cases of COVID-19 discharged during above period of 14 days were included in the study. Results: Total 352 cured asymptomatic COVID-19 patients were discharged from dedicated covid care center. Of these 352 subjects, 208 (59.09%) were males and 144 (40.91%) were females (p<0.05). 315 (89.49%) cured patients were in the age group of 18-60 years. 20 (05.68%) subjects were above 60 years of age. The mean and SD of the age of the subjects was 37.53 and 14.09 years respectively. The median age of the subjects was 35 years. Conclusions: It is very important to identify the asymptomatic patients in the community and to study their socio-demographic characteristics as early as possible through active public health strategies like surveys, testing and tracing. Such cases of COVID-19 should be isolated in DCCC and managed on a priority basis in order to prevent and control the infection.